2011
DOI: 10.1016/j.jad.2011.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Flourishing or floundering? Prevalence and correlates of anxiety and depression among a population-based sample of adult cancer survivors 6months after diagnosis

Abstract: Although lower than previously reported, psychological morbidity is prevalent six months after a cancer diagnosis and emphasises the need for routine psychosocial assessment throughout the cancer trajectory to identify those at increased risk or in need of immediate intervention. Physical activity, smoking cessation and coping skills training interventions warrant further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 43 publications
3
77
0
1
Order By: Relevance
“…Approximately 18 to 20 percent of long-term cancer adult survivors report anxiety symptoms. 3235 Using the Hospital Anxiety and Depression Scale with a cohort of survivors 6 and 12 months post-diagnosis, 22% and 21% respectively were higher than the cutpoint of 8. 33 Having higher scores at 6 months predicted higher scores at 12 months.…”
Section: Anxiety and Depression In Different Populations Of Survivorsmentioning
confidence: 97%
See 2 more Smart Citations
“…Approximately 18 to 20 percent of long-term cancer adult survivors report anxiety symptoms. 3235 Using the Hospital Anxiety and Depression Scale with a cohort of survivors 6 and 12 months post-diagnosis, 22% and 21% respectively were higher than the cutpoint of 8. 33 Having higher scores at 6 months predicted higher scores at 12 months.…”
Section: Anxiety and Depression In Different Populations Of Survivorsmentioning
confidence: 97%
“…Other identified risk factors for anxiety in adult survivors have included shorter time since diagnosis and a higher number of comorbid conditions, 36 as well as younger age, living alone and a diagnosis of lung cancer or melanoma. 35 A prospective, longitudinal study that documented trajectories of mood symptoms over time found 4 different trajectories in breast cancer survivors assessed over a 2 year follow-up: 1) High Stable, 2) High Decrease, 3) Mild Decrease and 4) Low Decrease. 37 Financial difficulties, lower global health and functional status were predictive of being in the High Stable trajectory.…”
Section: Anxiety and Depression In Different Populations Of Survivorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, patients with higher levels of flourishing tend to recover faster from illness and are less likely to fall into a relapse (Keyes, 2010). Although Keyes' model on human flourishing is widely accepted as an acceptable model for predicting happiness or human flourishing, little applied research exists regarding its utilisation in intervention studies (Boyes, Girgis, D'Este, & Zueca, 2011).…”
Section: Models For Promoting Happinessmentioning
confidence: 99%
“…In a study of testicular cancer survivors, 19.2% screened positive for an anxiety disorder (Dahl et al, 2005). Similarly, 24% of a sample of survivors with heterogeneous cancer types had significant levels of anxiety (Boyes, Girgis, D’Este, & Zucca, 2011). …”
mentioning
confidence: 99%